A rapid and simple non-radioactive assay for measuring uptake by solute carrier transporters - Song, Kunling; Zhang, Longbin; Fu, Xian; Li, Linfeng; Zhu, Gaolin; Wu, Mingjun; Zhang, Wei; He, Jia; Zhu, Sanyong; Dang, Yongjun; Liu, Jun-Yan; Chen, Chang; et al. (Frontiers in Pharmacology, 2024)
The solute carrier (SLC) transport proteins are the biggest family of transporters which mediate nutrient and metabolite cellular homeostasis. SLCs are associated with many human diseases and therefore they are potential therapeutic drug targets. However, SLCs are relatively understudied, partially due to lack of suitable tools, especially cell-based substrate uptake assays, to investigate their biological roles and for drug discovery. Although several cell-based substrate uptake assays have been reported, these assays suffer from numbers of disadvantages including hazardous radiolabeled substrates and limited availability of fluorescent biosensors, highlighting the need for the development of novel cell-based substate uptake assays. In this study, we developed a rapid, simple, and environmental-friendly cell-based uptake assay by using a stable isotope labeled compound as the SLC substrate and LC-MS/MS as the detection method. The assay was successfully employed to detect substrate uptakes by two SLCs, named L-type amino acid transporter 1 (LAT1, encoded by SLC7A5) and sodium taurocholate co-transporting polypeptide (NTCP, encoded by SLC10A1). Importantly, the assay yields similar results when compared with the radioactive method. Moreover, the assay was applied to screen for novel inhibitors of NTCP and one compound was found as a potential NTCP inhibitor. Taken together, these results demonstrate that our assay could be a new tool to investigate SLCs′ biological role and for drug discovery.